King of Warka Sen-Kashd: his urban achievements (1865-1833 BC) - Mohamed, Wasan Jasim (Al-Adab Journal, 2021)
The research deals with one of the royal personalities that had an important influence in the history of ancient Mesopotamia. This figure is represented by King Sen_kashd (Sin-kasid), who was headed as ruler of the ancient Babylonian era (2004_1595 BC) .in the city of Warka in particular and Mesopotamia in general, due to his political and urban achievements, his liberation of Warka comes from the control and influence of the king of the contemporary city of Larsa for Warka, and then his establishment of a ruling dynasty under his leadership to rule Warka independently starting from about 1860 BC.